1998
DOI: 10.1128/aem.64.7.2743-2747.1998
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Extracellular Polymeric Substances fromThiobacillus ferrooxidansfor Bioleaching

Abstract: Leaching bacteria such as Thiobacillus ferrooxidansattach to pyrite or sulfur by means of extracellular polymeric substances (EPS) (lipopolysaccharides). The primary attachment to pyrite at pH 2 is mediated by exopolymer-complexed iron(III) ions in an electrochemical interaction with the negatively charged pyrite surface. EPS from sulfur cells possess increased hydrophobic properties and do not attach to pyrite, indicating adaptability to the substrate or substratum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
159
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(168 citation statements)
references
References 23 publications
6
159
0
3
Order By: Relevance
“…For the iron oxidizing bacteria A. ferrooxidans growing on ferrous iron a value of 250 6 30 (lg EPS/10 10 cells) was experimentally obtained. 21 Considering a cell weight of 10 213 (g/cell) and a composition of 75% water in the cell weight, a value of f EPS 5 0.86 (g EPS /GDW) is obtained.…”
Section: Specific Reaction Ratesmentioning
confidence: 99%
“…For the iron oxidizing bacteria A. ferrooxidans growing on ferrous iron a value of 250 6 30 (lg EPS/10 10 cells) was experimentally obtained. 21 Considering a cell weight of 10 213 (g/cell) and a composition of 75% water in the cell weight, a value of f EPS 5 0.86 (g EPS /GDW) is obtained.…”
Section: Specific Reaction Ratesmentioning
confidence: 99%
“…This process may explain the accumulation of trace metals at depth, especially in the reactive relative to the pyrite fraction, because formation of iron sulfides is hindered by lack of reactive Fe. Interestingly, Gehrke et al (1998) found that EPS are involved in metal sulfide (e.g., pyrite) dissolution through the attachment of lipopolysaccharide-containing EPS to the sulfide substrate. The process is mediated by exopolymer-complexed Fe(III) ions that allow the establishment of an electrochemical interaction with the negatively charged pyrite surface.…”
Section: Enrichment Factorsmentioning
confidence: 99%
“…Growth on sulphide minerals is facilitated by close bacteriamineral interaction (Duncan & Drummond, 1973;Tributsch, 1976;Bennet & Tributsch, 1978;Norman & Snyman, 1987;Rodriguez & Tributsch, 1988;Southam & Beveridge, 1992). It has also been demonstrated that these bacteria are tightly bound to the mineral surface (Gormley & Duncan, 1974;Southam & Beveridge, 1992), via lipopolysaccharides (Southam & Beveridge, 1993;Arrendondo et al ., 1994;Gehrke et al ., 1998) suggesting that this interaction is important to the growth of thiobacilli on sulphides. Even though thiobacilli are closely associated with the sulphide mineral surface, bio-oxidation occurs through an indirect oxidation, in which bacteria utilize soluble reduced iron and sulphur species (Sand et al ., 1995;Nordstrom & Southam, 1997;Fowler & Crundwell, 1998).…”
Section: Introductionmentioning
confidence: 99%